Gender (in)equality among employees in elder care: implications for health - Elwér Sofia; Aléx Lena; Hammarström Anne (BMC, 2012)
Abstract Introduction Gendered practices of working life create gender inequalities through horizontal and vertical gender segregation in work, which may lead to inequalities in health between women and men. Gender equality could therefore be a key element of health equity in working life. Our aim was to analyze what gender (in)equality means for the employees at a woman-dominated workplace and discuss possible implications for health experiences. Methods All caregiving staff at two workplaces in elder care within a municipality in the north of Sweden were invited to participate in the study. Forty-five employees participated, 38 women and 7 men. Seven focus group discussions were performed and led by a moderator. Qualitative content analysis was used to analyze the focus groups. Results We identified two themes. "Advocating gender equality in principle" showed how gender (in)equality was seen as a structural issue not connected to the individual health experiences. "Justifying inequality with individualism" showed how the caregivers focused on personalities and interests as a justification of gender inequalities in work division. The justification of gender inequality resulted in a gendered work division which may be related to health inequalities between women and men. Gender inequalities in work division were primarily understood in terms of personality and interests and not in terms of gender. Conclusion The health experience of the participants was affected by gender (in)equality in terms of a gendered work division. However, the participants did not see the gendered work division as a gender equality issue. Gender perspectives are needed to improve the health of the employees at the workplaces through shifting from individual to structural solutions. A healthy-setting approach considering gender relations is needed to achieve gender equality and fairness in health status between women and men.